The impact of indoor pollution on asthma‐related outcomes: A systematic review for the EAACI guidelines on environmental science for allergic diseases and asthma - Agache, Ioana; Canelo‐Aybar, Carlos; Annesi‐Maesano, Isabella; Cecchi, Lorenzo; Biagioni, Benedetta; Chung, Fan; D'Amato, Gennaro; Damialis, Athanasios; Del Giacco, Stefano; De las Vecillas, Leticia; Dominguez‐Ortega, Javier; Galàn, Carmen; et al. (Allergy (Copenhagen), 2024)
Systematic review using GRADE of the impact of exposure to volatile organic compounds (VOCs), cleaning agents, mould/damp, pesticides on the risk of (i) new‐onset asthma (incidence) and (ii) adverse asthma‐related outcomes (impact). MEDLINE, EMBASE and Web of Science were searched for indoor pollutant exposure studies reporting on new‐onset asthma and critical and important asthma‐related outcomes. Ninety four studies were included: 11 for VOCs (7 for incidenceand 4 for impact), 25 for cleaning agents (7 for incidenceand 8 for impact), 48 for damp/mould (26 for incidence and 22 for impact) and 10 for pesticides (8 for incidence and 2 for impact). Exposure to damp/mould increases the risk of new‐onset wheeze (moderate certainty evidence). Exposure to cleaning agents may be associated with a higher risk of new‐onset asthma and with asthma severity (low level of certainty). Exposure to pesticides and VOCs may increase the risk of new‐onset asthma (very low certainty evidence). The impact on asthma‐related outcomes of all major indoor pollutants is uncertain. As the level of certainty is low or very low for most of the available evidence on the impact of indoor pollutants on asthma‐related outcomes more rigorous research in the field is warranted.